HADITH REVIEW ON DOMESTIC VIOLENCE IN MARRIAGE - Sri Ayu Andari Putri Alwaris; Sitti Aisyah Kara; Abdul Rahman Sakka (Multidisciplinary Indonesian Center Journal (MICJO), 2025)
In essence, Islam teaches to treat women in a good way . However, it cannot be denied that there are several factors that cause domestic violence. This type of research uses the sharia juridical approach method. This approach is defined as an approach that leads to the question of whether or not something can be used according to Islamic law . The data used in compiling this research is using references from journals, books and other articles related to the topic discussed. Domestic violence is an act that is not permitted to occur in building a household. Whatever form of domestic violence there is, a husband must not do anything that could hurt his wife.